Effects of isotopic neutron emission on silicon substrate - Roslan bin Yahya (Kulliyyah of Engineering, International Islamic University Malaysia, 2009)
The use of silicon material in electronic devices has grown rapidly and efforts have been made to develop techniques for growing perfect Si crystal with increasing dimension. Nonetheless, for the power devices to work at designated power levels and voltage reading, it is necessary to dope the silicon with impurities that make possible current flow through the bulk of the silicon. In conventional methods, thermodynamics play an important role since nearly all impurities of interest have distribution coefficients much less than unity. In contrast, the role played by the thermodynamics is negligible for Neutron Transmutation Doped (NTD) since there is no heating process involved. In NTD process, irradiation-induced Phosphorous atoms are created by means of neutron capture by a 30Si atom and forming the unstable 31Si isotope. This 31Si subsequently transmutes to 31P by β- emission and indirectly create phosphorous-doped silicon. In this study, silicon substrates have been irradiated by californium-252. Instead of using neutron source from nuclear reactor, isotopic neutron source has been used to irradiate the silicon in order to obtain neutron transmission doped silicon. The irradiation time varies at every 24 hours, starting from 24 hours (1 day) up to 144 hours (6 days). In conjunction of NTD process, microstructure of irradiated silicon will be examined by using Field Emission Scanning Electron Microscope (FESEM), the concentration of the impurities (phosphorous) will be monitored by using Energy Dispersive Spectroscopy (EDS) system and the hardness of the irradiated silicon will be measured by using nanoindentation test. Result shows that there is no significant change in hardness after irradiation. However, phosphorus impurities have increased due to longer irradiation time. Besides that, irradiation process also has change the microstructure of silicon and this can be clearly seen on six days irradiation time.